Dynamics of fluid-structure interaction in paintbrush - Moon, Seokmin; Ha, Jonghyun (Physics of Fluids, 2024)
Fluid-structure interactions are fundamental in both natural phenomena and industrial applications, particularly in dip-coating processes where withdrawal velocity and drainage dynamics are crucial. Understanding these interactions is essential for optimizing various processes, from enhancing the efficiency of industrial coatings to developing advanced materials with tailored properties. Here, we examine the capillary-induced dynamics of fiber bundles using paintbrush-like structures. We submerge fiber bundles in water and withdraw them at various velocities, observing that water trapped within the bundles leads to capillary-driven fiber assembly. Our experiments show that the bundle diameter after emergence increases with higher withdrawal speed due to viscous effects. We develop a theoretical model that accurately predicts the dynamics of fiber assembly driven by capillary and viscous flows. The mathematical model agrees well with our experimental results, demonstrating the complex interplay between capillary forces and fiber packing. We anticipate that our findings improve the understanding of fluid-structure interactions in fibrous media, providing physical insights that can be applied to more complex systems such as nanopattern collapse and nano/micro-manufacturing.
Keywords: Advanced materials; Dip-coating process; Fiber assemblies; Fibre bundle; Fluid-structure interaction; Industrial coatings; Natural phenomenon; Tailored properties; Theoretical modeling; Viscous effect